Multitask preoperative language mapping in epilepsy surgery: A combination of navigated transcranial magnetic stimulation and extra-operative electrical cortical stimulation. (September 2020) - Zhang, Xi; Zhang, Guojun; Yu, Tao; Xu, Cuiping; Yan, Xiaoming; Ma, Kai; Du, Wei; Gao, Runshi; Li, Yongjie
Highlights: To apply multitask nTMS is necessary in preoperative language mapping for epilepsy patients. We compared two extraoperative procedures (nTMS and eoECS) to overcome the limitations of intraoperative language testing. The validation with pre- to postoperative language assessments helps to improve the multitask design of nTMS mapping. Abstract: Navigated transcranial magnetic stimulation (nTMS) is increasingly applied in language mapping. However, the application mode and task selection of nTMS are not standardized. The aim of this study was to assessed the necessity and validity of multitask nTMS language mapping by comparing results with extraoperative electrical cortical stimulation (eoECS). In this study, sixteen epilepsy surgery patients were examined by nTMS and eoECS language mapping, and the two results were compared. The mapping results were validated with pre- to postoperative language assessments. Compared with eoECS, nTMS showed the overall sensitivity of 82.4%, specificity of 95.1%, positive predictive value of 66.7%, and negative predictive value of 97.8%. Spontaneous speech was the most sensitive task in the frontal area, naming was the sensitive task in both frontal and temporal areas. The false responses were mainly located in the perisylvian region. Multitask nTMS helps to reduce missing language relevant cortex preoperatively. Selecting spontaneous speech and naming tasks in frontal area, comprehension and naming tasks in temporal and posterior language area would strike the balance between the validity and efficiency of the mapping procedure. These results manifested the necessity of applying multitask in nTMS language mapping. Our study highlighted the importance of the nTMS evaluation mode and task selection for epilepsy patients.